The association between digit ratio (2D:4D) and the first spermatorrhea among Chinese boys. (March 2018) - Li, Ting; Wu, Lu; Wang, Yujie; Yao, Rongying; Meng, Yanqiu; Zhang, Yifei; Li, Zhiqiang; Zhou, Yanni; Han, Hui; Fu, Lianguo
Abstract: Background: The second-to-fourth digit ratio (2D:4D) is a marker of prenatal hormone exposure, which is negatively correlated with prenatal androgen and positively correlated with prenatal estrogen. The study was to analyze the association between 2D:4D and the first spermatorrhea to indirectly show the possible role of prenatal hormone during puberty development among boys. Method: The total of 367 boys aged 8–15 years were enrolled by using the stratified cluster sampling method. The variables of index finger (2D), ring finger (4D), height, weight, waist circumference (WC), skinfold thickness, testosterone and estradiol were measured, and the age at the first spermatorrhea was surveyed. Results: The average age at the first spermatorrhea was 12.15 years. The 2D:4D was not related to first spermatorrhea, circulating testosterone in boys ( P  > 0.05), however, was positively correlated with circulating estradiol ( P  < 0.05). The direct association ( OR value) between 4D, average of index finger and ring finger (AIR) and first spermatorrhea were 2.79 and 2.29, and the mediating effect ( OR value) of which were 1.95 and 2.01 by testosterone, accounting for 41.18% and 46.73% of the total effect, respectively. The 2D, MIDRL, lean body mass (LBM) were indirectly related to first spermatorrhea by testosterone, the mediating effects ( OR value) were 2.11, 1.71 and 2.41, respectively. Conclusion: The prenatal androgen exposure may be directly and indirectly related to first spermatorrhea. In addition, the high prenatal estrogen exposure may be indirectly associated with first spermatorrhea by testosterone. Highlights: We investigated the association between digit ratio (2D:4D) and the first spermatorrhea in Chinese boys. There was no correlation between 2D:4D and the first spermatorrhea. High prenatal androgen exposure may be directly and indirectly related to the first spermatorrhea. High prenatal estrogen exposure may be indirectly associated with the first spermatorrhea by testosterone. We have developed the novel index named Multiplying index of digit ratio and length (MIDRL) for the first time.